Eco-Innovation in Bi-Metallic Oxides: Pioneering Solutions for Dye Contamination and Bacterial Challenges - Radhalayam, D (Springer, 2025)
This study delineates the synthesis of bimetallic bismuth nickel oxide (BNO) nanoparticles employing a microwave combustion method that integrates a green synthesis approach using Trachyspermum ammi (Ajwain) seed extract. The nanoparticles were subjected to an exhaustive suite of analytical techniques to assess their morphological, structural, optical, and electronic characteristics. Techniques utilized included scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-diffuse reflectance spectroscopy (DRS), Fourier transform infrared spectroscopy (FTIR), and X-ray photoelectron spectroscopy (XPS). Photocatalytic performance of the synthesized BNO nanoparticles was evaluated through the degradation of Malachite Green (MG), a prevalent synthetic dye and notable aquatic contaminant. The nanoparticles exhibited a photodegradation efficiency of 97.18% for MG, following pseudo-first-order kinetics with a rate constant of 0.04669 min− 1. The degradation mechanism was elucidated through the scavenging of reactive oxygen species, particularly superoxide (O₂•-) and hydroxyl radicals (•OH), identifying them as the primary reactive species. In addition to photocatalytic activities, the BNO nanoparticles were tested for antibacterial efficacy of 93.97% and 96.69% against two bacterial strains such as Enterococcus faecalis (Gram-positive) and Escherichia coli (Gram-negative) respectively, demonstrating significant antibacterial properties. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.